EFL Learners’ Command of English Collocation - Lubis, Syahron (Talenta Publisher, 2019)
Indonesian learners when learning English as a foreign language often make mistakes in collocation. The collocation mistakes may be due to the ignorance of collocation and the transfer of collocation of their first language, Indonesian to English. The aim of the present study is to find out the command of English collocation by the Third Year students of SMA Bhayangkari 1, Medan. Before teaching them English collocation, a pretest on collocation is administered and after the teaching of collocation a post-test on collocation is administered in order to find out if their command of collocation increases. Findings show that there is an increase of score 4.425. The average score of the students’ command of collocation is 65.78 out of 100 as the maximum score. It can be concluded that the students’ mastery of collocation is still moderate. Therefore an extensive teaching of collocation for the students is still needed.